(untitled) (Revista Espinhaço, 2015)
The distinct views regarding the Serra do Cipó and the absence of a more comprehensive definition of the region cause inconsistencies in the boundaries of the study area. In general, the term “Serra do Cipó” can have several meanings: a district, a National Park, an Environmental Protection Area, a catchment area, a Tourist Circuit, among others. Based on complex analysis, the objective of this article is to present a definition of the region that matches its main characteristics and the natural and human elements of the Serra do Cipó. For this, a regional cutout was proposed to the Serra do Cipó overlapping historical, environmental, territorial, cultural and socioeconomic elements. Currently, tourism is the agent that most contributes to consolidate the image of the Serra joining mainly to environmental issues. Thus, the region was defined as the area comprised of the municipalities in which the sum of factors is present and thus strengthen the "Serra do Cipó" identity.